2020
DOI: 10.3390/cancers12040971
|View full text |Cite|
|
Sign up to set email alerts
|

Aspartate-β-Hydroxylase: A Promising Target to Limit the Local Invasiveness of Colorectal Cancer

Abstract: Colorectal cancer’s (CRC) ability to invade local tissues and lymph nodes and generate distant metastases is the key for TNM classification. Aspartate-β-hydroxylase (ASPH), a transmembrane protein that catalyzes Notch receptors and ligand activation, is involved in tumor invasion. Because Notch is involved in gut homeostasis, it could be a target for CRC therapy. ASPH mRNA and protein expression, promoter methylation and gene copy numbers were evaluated using the TCGA and CPTAC human CRC datasets. Using digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…In the study by Kadota et al [55], the ASPH gene locus has been identified as one of the DNA regions with focal amplification in primary breast cancer. In colorectal cancer, ASPH gain or amplification was found in 56% of samples [56]. Next, a suppressant role of the microRNA miR-200a in posttranscription regulation of the ASPH expression in hepatoma cells has been found [57].…”
Section: Localization In Cells Tissue Distribution and Expression Rmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Kadota et al [55], the ASPH gene locus has been identified as one of the DNA regions with focal amplification in primary breast cancer. In colorectal cancer, ASPH gain or amplification was found in 56% of samples [56]. Next, a suppressant role of the microRNA miR-200a in posttranscription regulation of the ASPH expression in hepatoma cells has been found [57].…”
Section: Localization In Cells Tissue Distribution and Expression Rmentioning
confidence: 99%
“…Oncogenic abilities of ASPH have been experimentally demonstrated using tumor cell lines and mouse and rat models of different types of human tumors with ASPH overexpression, including cholangiocarcinoma [ 4 , 44 , 75 , 87 , 88 ], hepatocellular carcinoma [ 5 , 37 , 38 , 57 , 62 , 70 , 73 ], neuroblastoma [ 30 ], pancreatic cancer [ 7 , 41 , 43 , 71 ], glioma [ 6 ], breast carcinoma [ 42 ], castration-resistant prostate cancer [ 66 ], and colorectal cancer [ 56 ]. In studies analyzing ASPH function, various approaches were utilized to reveal signaling pathways affected by ASPH.…”
Section: Asph As a Therapeutic Targetmentioning
confidence: 99%
“…CRC is the fourth most deadly cancer, with ~900,000 deaths annually worldwide in 2019 ( 80 ). A bioinformatics analysis revealed that the mRNA and protein levels of AspH are upregulated in CRC compared with in normal tissues due to gene copy number variations and promoter demethylation ( 81 ). AspH accumulates at the invasive tumor margin, which may be associated with cell invasion and infiltration ( 81 ).…”
Section: Asph Expression In Various Types Of Cancermentioning
confidence: 99%
“…A bioinformatics analysis revealed that the mRNA and protein levels of AspH are upregulated in CRC compared with in normal tissues due to gene copy number variations and promoter demethylation ( 81 ). AspH accumulates at the invasive tumor margin, which may be associated with cell invasion and infiltration ( 81 ). It has been recently reported that Notch signaling recruits TGFβ-dependent neutrophils to drive CRC metastasis; this pathway has an important role in the tumor microenvironment and predicts a poor survival in patients with CRC ( 82 ).…”
Section: Asph Expression In Various Types Of Cancermentioning
confidence: 99%
See 1 more Smart Citation